The prevalence of anxiety symptoms in patients with vaginismus referred to a private psychiatric clinic in Tehran (2001-2002) - M Amin Esmaeli; M Azar; C Iranpour (JRI, 2003)
Sexual behavior as a response to biological instinct is essential for survival, and affects ones’ satisfaction from marital life. The prevalence of sexual dysfunction reaches 30-50% in both sexes. It can be of adverse consequences on the couples’ life. Vaginismus is one of the frequently observed sexual dysfunctions in women. It is accompanied by anxiety, phobia and avoidance reactions. The aim of this study is to assess the prevalence of anxiety features in patients suffering from vaginismus. Symptom check list-90 questionnaire was given to 27 patients diagnosed as vaginismus by Gynecologist referred to in a private psychiatric clinic. “Generalized anxiety, phobia and obsession-compulsion” subscales of SCL-90 questionnaire were particularly investigated. Data were analyzed by Chi-Square and Fisher’s exact tests. According to SCL-90 scores, 13 patients (48.1%) suffered from generalized anxiety, 10 patient (37%) from phobia and 19 patient (70.4%) from obsession-compulsion symptoms. The results were consistent with those of other studies on this subject. Integrated approach to vaginismus consisting of both psycho therapy and pharmacotherapy is there fore recommended.
Keywords: Generalized anxiety, Phobia, Obsession- compulsion, Vaginismus, Sexual dysfunction